Environmental policy of the Black Sea region: Current state and development prospects - Alyona A. Baksheeva (Russian Studies in Law and Politics, 2025)
The article examines key aspects of the Black Sea region's environmental policy, including the impact of anthropogenic activities on ecosystems, climate change and water pollution, which are relevant to the environmental agenda of the 21st century. The purpose of the study is to examine the effectiveness of environmental policies of the Black Sea region states. The current international agreements and initiatives aimed at protecting biodiversity and sustainable development are analyzed. The possibilities of cooperation between the Black Sea basin states in the field of environmental protection and natural resource management are being assessed. Recommendations are given on strengthening environmental responsibility and the introduction of effective mechanisms for monitoring and assessing the impact on nature. The comparative research method is used, as well as the analysis, synthesis and classification of environmental policies. The article highlights the need to integrate environmental aspects into economic planning and regional policy development. It is concluded that it is necessary to synthesize and consolidate the efforts of the states of the Black Sea region to improve the ecological and political situation in the Black Sea.